Empowering MSMEs Through Optimizing Social Media Content Creation Skills to Increase Sales in Pekik Nyaring Village, Pondok Kelapa District, Central Bengkulu Regency - Apri Andani; Arma Putra; Indra Cahyadinata; Ketut Sukiyono; Melli Suryanty (Talenta Publisher, 2026)
This community service program aims to improve the skills of MSMEs in Pekik Nyaring Village, Pondok Kelapa District, Central Bengkulu, in creating social media content as a digital marketing strategy. This village, which has potential for processed agricultural products such as elephant ear chips, banana chips, rengginang (rice crackers), and various cassava products, still faces limitations in utilizing social media as a promotional tool. Activities were carried out through observation, digital content management counseling, content planning and creation training, and digital administration. The training emphasized hands-on practice in product photography, lighting, visual composition, image editing using mobile apps, as well as creating captions, hashtags, and content calendars. Results showed significant improvements in participants' ability to produce upload-ready content and understand basic digital marketing strategies. Despite obstacles such as varying device quality, limited internet access, and limited technical skills, the adaptive approach successfully ensured all participants could optimally follow the process. The program has had a positive impact on improving MSMEs' readiness to promote their products independently on social media. Going forward, further training in graphic design is essential so that participants can create more attractive, professional, and uniform content templates and frameworks to increase product competitiveness.